IMPLEMENTASI COLLABORATIVE STRATEGIC READING (CSR) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS VIIC SMP PGRI 2 DENPASAR TAHUN AJARAN 2022/2023 - Rosari, Maria Sri; Wedasuwari, Ida Ayu Made; Sukanadi, Ni Luh (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2024)
This research is a class action research (PTK) with goal 1. To improve the reading comprehension of grade VIIC students of SMP PGRI 2 Denpasar for the 2022/2023 academic year; (2) knowing the steps for implementing the Colllaborative Strategic Reading (CSR) learning method to improve the reading comprehension of grade VIIC students of SMP PGRI 2 Denpasar for the 2022/2023 academic year. Data collection is carried out by observation and test methods. The data obtained were analyzed descriptively, qualitatively and quantitatively. The results showed that the application of CSR methods can improve reading comprehension skills of grade VIIC students of SMP PGRI 2 Denpasar. The pre cycle results showed that 40 students had an average standard score of 4.42 still on the criteria of lacking, the score was still relatively low and needed to be improved to the next cycle by improving teaching. In cycle I has increased with an average score of 5.92 with sufficient category In cycle II the test results of increased reading comprehension ability reached an average value of 6.9 with more than enough category. In cycle III the test results for improving reading comprehension skills reached an average score of 8.15 with a good category, this average score has met the KKM value of 7.5. The steps for implementing the CSR method: the teacher divides students into groups, previewing, click and clunk, getting the gist, wrap-up and the teacher assigns students to make summaries based on texts that have been read and understood. Abstrak Penelitian ini merupakan penelitian tindakan kelas (PTK) yang berutujuan 1. Untuk meningkatkan kemampuan membaca pemahaman siswa kelas VIIC SMP PGRI 2 Denpasar; (2) mengetahui langkah-langkah penerapan metode pembelajaran Colllaborative Strategic Reading (CSR) untuk meningkatkan kemampuan membaca pemahaman siswa kelas VIIC SMP PGRI 2 Denpasar tahun ajaran 2022/2023. Pengumpulan data dilakukan dengan metode observasi dan tes. Data yang diperoleh dianalisis secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukan bahwa penerapan metode CSR dapat meningkatkan kemampuan membaca pemahaman siswa kelas VIIC SMP PGRI 2 Denpasar. Hasil prasiklus menunjukan bahwa 40 peserta didik memiliki nilai rata-rata skor standar sebesar 4,42 masih pada kriteria kurang, nilai tersebut masih tergolong rendah dan perlu adanya peningkatan ke siklus selanjutnya dengan memperbaiki pengajaran. Pada siklus I sudah mengalami peningkatan denga nilai rata-rata 5,92 dengan kategori cukup Pada siklus II hasil tes peningkatan kemampuan membaca pemahaman mencapai nilai rata-rata 6,9 dengan kategori lebih dari cukup. Pada siklus III hasil tes peningkatan kemampuan membaca pemahaman mencapai nilai rata-rata 8,15 dengan kategori baik, nilai rata-rata ini sudah memenuhi nilai KKM yaitu 7,5. Adapun Langkah-langkah penerapan metode CSR: guru membagi siswa dalam bentuk kelompok, previewing (curah pendapat), click and clunk, getting the gist, wrap-Up dan guru menugaskan siswa membuat ringkasan berdasarkan teks yang telah dibaca dan dipahami.